The effects of childhood maltreatment on adolescent non-suicidal self-injury behavior: mediating role of impulsivity - Li, Xi; Liu, Xiao-Li; Wang, Yu-Jing; Zhou, Dong-Sheng; Yuan, Ti-Fei (Frontiers in Psychiatry, 2023)
Background: Non-suicidal self-injury (NSSI) severely challenges mental health in adolescents. Childhood maltreatment experience acts as high-risk factor for adolescents to engage in NSSI behaviors. On the other hand, impulsivity or loss of control sets the threshold for NSSI execution. Here we examined the effects of childhood maltreatment on adolescent NSSI-related clinical outcomes and the potential role of impulsivity. Methods: We assessed the clinical data of 160 hospitalized NSSI adolescents and recruited 64 age-matched healthy subjects as a control group. The clinical symptoms of NSSI are expressed by the NSSI frequency, depression, and anxiety measured by the Ottawa Self-Injury Inventory, the Beck Depression Inventory, and the Beck Anxiety Inventory. Childhood maltreatment and impulsivity were assessed with Childhood Trauma Questionnaire and Barratt Impulsiveness Scale. Results: The results showed that when compared to HC group, NSSI group is more likely to experience childhood maltreatment. Notably, NSSI group with Childhood maltreatment accompanies higher trait impulsivity and exacerbated clinical outcomes, such as NSSI frequency, depression and anxiety symptoms. Mediation analyses indicated that the association between childhood maltreatment and NSSI-related clinical outcomes was partially explained by impulsivity. Conclusions: We found that NSSI adolescents have a higher proportion of childhood maltreatment. Impulsivity plays a mediating role between childhood maltreatment and NSSI behaviors.